L’intégration régionale vue par le prisme de la frontière Canada/États-Unis : l’entre-deux comme un processus remis en question par la politique de sécurisation post 9/11 - Pierre-Alexandre BEYLIER (E-REA)
In the wake of the 9/11 terrorist attacks, the Canada/US border experienced a rebordering phenomenon. It inserted a logic that was antagonistic to the logic of integration that the border had known for several decades. This article proposes to reflect on this phenomenon of integration through a theoretical analysis of the Canada/US border by applying different models in order to evaluate its degree of integration through a study of its different functions.